2011
DOI: 10.4414/smw.2011.13309
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent inflammatory factor production and NFκB activation in a rodent model of intermittent hypoxia

Abstract: The inflammatory response, manifested by serum levels of inflammatory factors and nuclear accumulation of activated NF-κB P65, was more serious in the IH group than in the SH and control group, and was dependent on hypoxia levels. This reaction increased initially and then decreased, which indicates the presence of compensatory mechanisms and an adaptive response to such stressors in the body. Notably, the correlation of NFκB activation to production of inflammatory factors under intermittent hypoxia implies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 22 publications
2
25
0
Order By: Relevance
“…It has been known that IH increases the levels of various inflammatory factors (Li et al, 2011) and we have reported that the serum levels of TNF-α and IL-6, as well as the phosphorylation of NF-κB were increased (Nishioka et al, 2013;Matsumoto et al, 2009;Yamashita et al, 2007). Increased levels of TNF-α and oxidative stress might promote the activation of NF-κB and the development of cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 90%
“…It has been known that IH increases the levels of various inflammatory factors (Li et al, 2011) and we have reported that the serum levels of TNF-α and IL-6, as well as the phosphorylation of NF-κB were increased (Nishioka et al, 2013;Matsumoto et al, 2009;Yamashita et al, 2007). Increased levels of TNF-α and oxidative stress might promote the activation of NF-κB and the development of cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 90%
“…We previously reported that chronic IH exposure with FiO2 nadir to 5 % for 30 s in rats results in an oxyhemoglobin desaturation of about 65 % [23]. After 4 weeks of IH exposure, rats exhibit pathological changes that mimic those found in OSA patients, such as systemic hypertension, endothelial dysfunction, and excess sympathetic activity.…”
Section: Discussionmentioning
confidence: 94%
“…Neutrophils activated by stimulation produce proinflammatory cytokines such as TNF-α, IL-6, and IL-8; on the other hand, IL-6 and IL-8 facilitate survival of neutrophils by inhibiting apoptosis [29]. In our previous study, we reported that serum concentrations of pro-inflammatory factors including TNF-α, IL-6, IL-8, and nuclear accumulation of activated NF-κB P65 were increased in rats exposed to IH and were dependent on the level of hypoxia [23]. In addition, some studies have shown that the late survival effect of TNF-α on human neutrophils involves activation of both the NF-κB and phosphoinositide 3-kinase (PI3K) pathways.…”
Section: Discussionmentioning
confidence: 97%
“…In the inactivated form, cytosolic NF-κB is bound to its corepressor molecule IκB. Stimulation, like hypoxia, causes degradation of IκB, releasing the subunits p50 and p65 to form the NF-κB heterodimer, which is translocated to the nucleus to activate target genes, including TNFα and other inflammatory factors [18]. Changes in transcriptional activity have been assigned to phosphorylation of the p65 subunit of NF-κB [19], suggesting that further inflammatory targets are triggered during oxidative stress [20].…”
Section: Introductionmentioning
confidence: 99%